Effect of Entrepreneurial Orientation in sustaining the success of Competitive Strategies: "Analytical research of the manager’s views of Ur State Company at Thi-Qar Governorate" - Hatief AL-Fatlawey, Miethak; Kadhum Brias, Ahmed; Gatea Atyiah, Abbas (Iraqi Journal for Administrative Sciences, 2024)
The research aims to explore the extent of impact of Entrepreneurial orientation to achieve the sustainability of competitive strategies successful, and in order to achieve that goal, a hypothetical scheme expressing two of the main hypotheses, has been subjected to multiple tests, the researchers used the questionnaire as a tool to obtain the necessary data for that test, by the descriptive approach analytical. Which has been applied in the Ur State Company at Thi-Qar Governorate, it questionnaire was distributed to a Purposive sample of (353) individuals, including managers of Departments, divisions, units, and teams. from the total employees (2728) individuals. The study adopted a number of statistical tools, including (Coefficient (Cronbach Alpha), Pearson correlation coefficient, and Structural Equation Modeling), as those statistical tools were implemented by using software (SPSS, V.23) and (Amos, V.20). The research reached a set of conclusions, the most prominent of which is that the Ur State Company shows great interest in Entrepreneurial orientation, as an influential element to achieve sustainability of competitive strategies successful. As for the most important recommendations that came out of the research, they are giving more attention to the Entrepreneurial orientation of Ur State Company, as it is an effective strategic tool at the competitive level, and it has a great role in sustaining the success of competitive strategies. Which is the main problem of the researched organization in the context of the competitors' exposure to its markets and trying to reduce its share in those markets.